2022
DOI: 10.1038/s41598-022-14643-7
|View full text |Cite
|
Sign up to set email alerts
|

Baseline conditions and nutritional state upon hospitalization are the greatest risks for mortality for cardiovascular diseases and for several classes of diseases: a retrospective study

Abstract: The aim of this retrospective study was to evaluate risk factors for 3-years mortality after hospital discharge in all inpatients admitted to a general hospital in Milano, Italy. A total of 2580 consecutive patients admitted to Ospedale San Paolo, July 1 to December 31, 2012, for several classes of diseases (internal medicine, cancer, infectious diseases, trauma and surgery, pneumonia, and heart diseases) were studied. Age, total disease, type of admission, length of admission, age-adjusted Charlson index, pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…The main results were as follows: among the four assessment tools, the AUC, PPV, and NPV of PNI and GNRI were signi cantly higher than those of CONUT and BMI; this nding is consistent with the results of other studies [18,29] . The PNI predicted the greatest incremental value of risk, with patients with low nutritional scores having a higher risk of MACE than those with high nutritional scores [30] . According to the calibration curves, the three prediction models constructed from PNI, GNRI, and CONUT had good calibration ability; the decision analysis curves (DCA) suggested that the models constructed from PNI and GNRI had high clinical validity, while the prediction model constructed from BMI had poor clinical validity.…”
Section: Discussionmentioning
confidence: 96%
“…The main results were as follows: among the four assessment tools, the AUC, PPV, and NPV of PNI and GNRI were signi cantly higher than those of CONUT and BMI; this nding is consistent with the results of other studies [18,29] . The PNI predicted the greatest incremental value of risk, with patients with low nutritional scores having a higher risk of MACE than those with high nutritional scores [30] . According to the calibration curves, the three prediction models constructed from PNI, GNRI, and CONUT had good calibration ability; the decision analysis curves (DCA) suggested that the models constructed from PNI and GNRI had high clinical validity, while the prediction model constructed from BMI had poor clinical validity.…”
Section: Discussionmentioning
confidence: 96%
“…Therefore, together with hospital admissions, exemptions were considered a proxy of development of chronic diseases. This procedure has previously been employed and validated [ 8 , 11 , 12 ].…”
Section: Methodsmentioning
confidence: 99%